THE IMPACT OF CONSUMERS PERCEIVED PRODUCT QUALITY TO INTENTION TO BUY SMOKED SEAFOOD THROUGH E-COMMERCE - Tian Nur Ma’rifat; Arief Rahmawan (Universitas Darussalam Gontor, 2023)
The increasingly massive use of e-commerce in Indonesia has encouraged producers of seafood products to market their products through e-commerce. One of the most popular seafood products in Indonesia is smoked seafood. Smoked seafood with unique product quality characteristics and simple production technology have wider marketing potential if marketed through e-commerce. Therefore, to develop smoked seafood products through e-commerce, this study aims to determine the relationship between perceived quality of smoked seafood products and consumer purchase intentions through e-commerce. The data collection method used was through online questionnaire with multiple linear regression analysis. The analysis resulted in the findings that the factor having most influences to the intensity of consumers in buying smoked seafood products through e-commerce is user display. The implication of the results is that attractive user interface on an e-commerce platform can enhance consumers' interest and purchase intensity. Smoked seafood producers who will market their product through e-commerce need to pay attention to the design of product displays and provide a positive user experience to boost sales of their products.